IDENTIFIKASI PIGMEN KAROTENOID PADA BAKTERI SIMBION RUMPUT LAUT Caulerpa cupressoides (Vahl) C. Agardh - Arlita, Nurul Ria; Radjasa, Ocky Karna; Santoso, Adi (977-2407769)
One of natural pigments besides Chlorophyll is carotenoid that has two classes, namely Xanthophyll and Carotene that have important roles for human helath like provitamin A, antioxidant, anticancer, and to improve the better immune responses. Carotenoids are yellow pigments, orange to red pigments that can be found in human, animals, high level plants, fruits, algae, fungi and bacteria. Bacterial symbionts produce pigments that are similar with their host. Pure cultures from marine microbial community can be isolated and cultivated in big scale in relatively short time. The purpose of this study was to as well as isolate and to identify pigments carotenoid from bacterial symbionts from seaweed Caulerpa cupressoides to identify bacterial symbionts that produce carotenoid pigments. Pigment analysis was performed by UVVis spectrophotometer and High Performance Liquid Chromatography (HPLC). Bacterial identification was performed based on biochemical tests. These results showed that from 13 bacterial symbionts isolated from Teluk Awur Waters, there was 2 isolates that positively synthesize carotenoids pigments, CJ.K and CJ.OR bacteria respectively, CJ.K bacterium contained of Violaxanthin and Neoxanthin pigments. While CJ.OR bacterium contained of Xanthophyll, Diadinoxanthin, Î³-carotene, and Î²-carotene pigments. Bacterial identification showed that CJ.K bacterium was Brevibacterium maris and CJ.OR bacterium was Paracoccus alcaliphilus. This result showed that found some carotenoid pigments from bacterial symbiont of seaweed Caulerpa cupressoides.